2020
DOI: 10.1192/bjo.2020.89
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of treatment resistance and clozapine use in early intervention services

Abstract: Background Treatment resistance causes significant burden in psychosis. Clozapine is the only evidence-based pharmacologic intervention available for people with treatment-resistant schizophrenia; current guidelines recommend commencement after two unsuccessful trials of standard antipsychotics. Aims This paper aims to explore the prevalence of treatment resistance and pathways to commencement of clozapine in UK early intervention in psychosis (EIP) services. Method Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
1
42
1
Order By: Relevance
“…Up to a third of individuals with schizophrenia show resistance to antipsychotic treatment (Elkis & Buckley, 2016; Lally, Gaughran, Timms, & Curran, 2016b; Mørup, Kymes, & Oudin Åström, 2020; Stokes et al, 2020), i.e. they do not respond adequately to two or more trials of antipsychotic medication, each lasting 4–6 weeks, at doses in at least the mid-point of the licensed therapeutic range (NICE guidelines; National Institute for Health and Care Excellence, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Up to a third of individuals with schizophrenia show resistance to antipsychotic treatment (Elkis & Buckley, 2016; Lally, Gaughran, Timms, & Curran, 2016b; Mørup, Kymes, & Oudin Åström, 2020; Stokes et al, 2020), i.e. they do not respond adequately to two or more trials of antipsychotic medication, each lasting 4–6 weeks, at doses in at least the mid-point of the licensed therapeutic range (NICE guidelines; National Institute for Health and Care Excellence, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, clozapine prescribing appears suboptimal, with at least a third of eligible patients at any given time not prescribed clozapine. Stokes et al (2020), 22 using data from the UK National Evaluation of the Development and Impact of Early Intervention Services study, showed slightly lower clozapine eligibility across EIP services (7.7%), and lower prescribing rates (2.4%) over a 12-month study period, highlighting the persistent underuse of clozapine and more commonly seen polypharmacy practice in this patient population. Important barriers to clozapine prescribing in an EIP service include tolerability, the need for good adherence, patient willingness and the requirement for regular blood monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Clozapine has long been recognised as underutilised, with its use in eligible early psychosis patients ranging from 2.4-16.3%. [19][20][21][22] Clozapine, although superior in efficacy compared with other antipsychotic medicines and effective in treatment-refractory schizophrenia patients, 23,24 also poses a challenge in terms of its potential side-effect profile, with the need for close monitoring and adherence to ensure safe prescribing. 25 Side-effects range from early and mostly benign (such as fever, sedation and tachycardia), to more serious, including haematological (neutropenia), cardiovascular (cardiomyopathy and myocarditis), neurological and metabolic.…”
mentioning
confidence: 99%
“…In clinical practice, switching to clozapine is highly recommended for the treatment of TRS patients [ 17 , 18 ]. However, the risk of metabolic adverse events, especially diabetes, among TRS patients is of increasing concern [ 19 22 ]. To date, few investigations have assessed clozapine-induced MetS in TRS patients.…”
Section: Side Effects Of Antipsychotic Drugsmentioning
confidence: 99%